The Pomegranate Deciduous Trait Is Genetically Controlled by a PgPolyQ-MADS Gene - Harel-Beja, Rotem; Ophir, Ron; Sherman, Amir; Eshed, Ravit; Rozen, Ada; Trainin, Taly; Doron-Faigenboim, Adi; Tal, Ofir; Bar-Yaakov, Irit; Holland, Doron (Frontiers in Plant Science, 2022)
The pomegranate (Punica granatum L.) is a deciduous fruit tree that grows worldwide. However, there are variants, which stay green in mild winter conditions and are determined evergreen. The evergreen trait is of commercial and scientific importance as it extends the period of fruit production and provides opportunity to identify genetic functions that are involved in sensing environmental cues. Several different evergreen pomegranate accessions from different genetic sources grow in the Israeli pomegranate collection. The leaves of deciduous pomegranates begin to lose chlorophyll during mid of September, while evergreen accessions continue to generate new buds. When winter temperature decreases 10o C, evergreen variants cease growing, but as soon as temperatures arise budding starts, weeks before the response of the deciduous varieties. In order to understand the genetic components that control the evergreen/deciduous phenotype, several segregating populations were constructed, and high-resolution genetic maps were assembled. Analysis of three segregating populations showed that the evergreen/deciduous trait in pomegranate is controlled by one major gene that mapped to linkage group 3. Fine mapping with advanced F3 and F4 populations and data from the pomegranate genome sequences revealed that a gene encoding for a putative and unique MADS transcription factor (PgPolyQ-MADS) is responsible for the evergreen trait. Ectopic expression of PgPolyQ-MADS in Arabidopsis generated small plants and early flowering. The deduced protein of PgPolyQ-MADS includes eight glutamines (polyQ) at the N-terminus. Three-dimensional protein model suggests that the polyQ domain structure might be involved in DNA binding of PgMADS. Interestingly, all the evergreen pomegranate varieties contain a mutation within the polyQ that cause a stop codon at the N terminal. The polyQ domain of PgPolyQ–MADS resembles that of the ELF3 prion-like domain recently reported to act as a thermo-sensor in Arabidopsis, suggesting that similar function could be attributed to PgPolyQ-MADS protein in control of dormancy. The study of the evergreen trait broadens our understanding of the molecular mechanism related to response to environmental cues. This enables the development of new cultivars that are better adapted to a wide range of climatic conditions